ANALISIS KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN PADA TOKO BE ONE TOP SANGATTA - Agustina Alinan; Saiful; Efendi Rahmanto (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this research is to find out how much influence product quality has on consumer buying interest. The type of research is quantitative research with the number of samples in this study as many as 101 respondents. The analytical tools used by the author are Multiple Regression analysis, Validity and Reliability Test, Hypothesis Testing, and Classical Assumption Test. The results of this study indicate that there is a positive and significant partial effect of product quality on Buying Interest at Be One Top Sangatta Stores. Based on the results of the hypothesis. The results of this study indicate that there is a partial influence of service quality which is not too significant according to the Sig Value on buying interest